Sulfate content in some water systems within Erbil City/KRG by using turbidimetric and titrimetric methods. - Shekha, Yahya Ahmed (Sulaimani Journal for Pure and Applied Sciences, 2015)
This study was conducted on two water bodies; three sites were selected on Erbil wastewater channel and four sites on Greater Zab river. Water samples were collected at regular monthly interval periods beginning at July 2012 to April 2013. Sulfate concentration was determined by EDTA titrimetric and barium sulfate procedures in order to compare the results obtained by both methods. The mean values of sulfate concentration in Greater Zab river was 74.98 and 1205.9 mg.l-1 for EDTA titrimetric and barium sulfate methods respectively, while for Erbil wastewater channel samples sulfate concentration mean values was 109.46 and 1240.5 mg.l-1 for EDTA titrimetric and barium sulfate methods respectively. As a mean values sulfate concentration is ten times more by barium sulfate method than other method. From standard error values it appears that EDTA titrimetric method is more accurate and suitable for sulfate determination than other method which is quick, simple and easy.
Keywords: Sulfate determination; turbidimetric method; EDTA titrimetric method; Greater Zab river; Erbil wastewater channel